Handover evaluation of UMTS-WiMAX networks - Saif A. Abdulhussein; Riyadh A. Abdulhussein (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Recently, data traffic movement through a wireless channel is assisted by suggesting and implementing many mechanisms, to achieve the speedy increasing importunity and popularity of the wireless networks. Various wireless technologies can be copulated to develop a heterogeneous network, which is a candidate towards (4G) networks. OPNET modeler (14.5) is used to design simulation modules of the heterogeneous network. During device connection between the worldwide interoperability for microwave access (WiMAX) and universal mobile telecommunication system (UMTS) networks, Performance metrics such as; Jitter end-to-end delay (E-2-E) Throughput is used. The results of the simulation are measured to determine the efficiency of the transfer using WiMAX-UMTS according to the selected metrics. The WiMAX-UMTS has shown valuable improvement in Process Durability, reduction of E-2-E delay, and Jitter. The maximum amount of data transfer and the least amount of delay and Jitter is at 250 sec. Because of the handover operations and data transfer momentum, the worst-case passes in the network when 618 sec is the minimum amount. The efficiency of throughput for WiMAX equal to 0.092666% as for the efficiency of throughput for UMTS equal to 4.633333*10-6 % whereas the E-2-E efficiency a delay equal to 0.5466%.